When death looks at us with a desire to take us to the tartarus (Revista revoluciones, 2020)
The entire planet has collapsed by the Covid-19-named pathogen, and death starred in its best horror episode to bring to the Tatar all those who still did not realize the life they had. The present aims to theoretically reflect the limit situations, the dire actions, the apparent realities, pathologies and devastating phenomena that brought the human species to the brink of extinction.
Keywords: Death; coronavirus; isolation; life; endurance